Dispersal of Egyptian Vultures Neophron percnopterus: the first case of long-distance relocation of an individual from France to Sicily. Issue 2 (1st December 2016) - Di Vittorio, M.; Henriquet, S.; Kobierzycki, E.; Luiselli, L.; Hema, E.M.; Murabito, L.; Rannisi, G.; López-López, P.
ABSTRACT: Knowledge of juvenile dispersal is important for understanding population dynamics and for effective conservation, particularly of geographically isolated raptor populations. Here, we report the first documented case of a long-distance movement of an Egyptian Vulture Neophron percnopterus from the French population to Sicily. This observation opens a new perspective for the conservation of the small and endangered Sicilian population of this species, providing evidence that persistence of the Italian population may be aided by new input from other countries.